Ultrastructural evidence for the activation of autophagy and analysis of the protective role of autophagy in goat spermatozoa under liquid storage - Tengfei Liu; Jincong Niu; Yuqi Huang; Hong Chen; Yongjie Wu; Yongping Xu (Frontiers in Veterinary Science)
Liquid storage of semen is a widely used technology for promoting genetic improvement in goat breeding. The short shelf life of spermatozoa greatly limits the application of liquid storage, which urgently needs to explore the underlying regulatory factors. Autophagy as a cellular catabolic process plays critical roles in eliminating damaged material, that thus protects the function and fertilizing ability of spermatozoa. Nevertheless, the regulatory mechanisms of autophagy in goat spermatozoa under liquid storage remain unclear. In this study, the typical morphologic abnormalities and ultrastructural changes in goat spermatozoa, such as plasma membrane swollen and shrunken, acrosome exfoliation, and axoneme exposure, were observed after liquid storage at 4°C. Moreover, assessment of the formation of autophagy in liquid-stored goat spermatozoa was performed by a morphological “gold standard” of electron microscopy. Notably, a large number of vesicles with double-membrane structure indicating autophagosome were found to surround the aberrant spermatozoa, suggesting the activation of autophagy. Several proteins, such as LC3, ATG5, and p62, exhibited differential expression after liquid storage, which further validated the occurrence of autophagy in liquid-stored goat spermatozoa. Furthermore, chloroquine treatment was used to inhibit the autophagy of spermatozoa, which caused a significantly decrease in the quality of liquid-stored spermatozoa, including motility, viability, plasma membrane integrity, and acrosome integrity. Significant increase in ROS and MDA levels of spermatozoa and significant decrease in Ca2+ influx and protein tyrosine phosphorylation of spermatozoa were also detected after chloroquine-induced autophagy inhibition. The ultrastructural observation of double-membrane autophagosome provides strong evidences for the activation of autophagy in goat spermatozoa under liquid storage. The inhibition of autophagy mediated by chloroquine indicated that autophagy plays vital roles in the survival of spermatozoa. These results facilitate understanding the activation of autophagy in spermatozoa and provide valuable references for uncovering the underlying regulatory mechanisms of liquid storage of goat spermatozoa.